Reselience Through Faith: Islamic Education As A Prespective Mental Reinforcement For School Children Who Come From Broken Homes - Khoirunnisa, Dinda; Nasikhin, Nasikhin (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2024)
This article explores the role of Islamic education as a mental reinforcement for schoolchildren who come from broken homes. This study used the qualitative method through interviews to gain in-depth insight into the influence of Islamic education on the perception and mental well-being of children from incomplete family backgrounds. With a focus on religious, moral, and spiritual values, this study aims to identify Islamic education strategies that can provide significant support for children in facing psychological challenges that may arise due to incomplete family conditions. The results of this study are expected to make an important contribution in the development of more holistic and sustainable education programs, especially for children who need additional support in overcoming the negative impacts of broken home situations.This research also found that the role of teachers and educators in the Islamic education environment is very crucial. Teachers not only act as teachers, but also as mentors and spiritual guides who provide positive examples for students. Close interactionbetween teachers and students creates a strong emotional bond, which is important for children's mental well-being. Overall, this research confirms the importance of Islamic education in providing mental and emotional support for children from Broken Homefamilies. It is hoped that the implementation of educational strategies that are integrated with Islamic values can help children develop stronger mental resilience and achieve better well-being. Thus, the findings from this research can be a basis for designing more effective and inclusive educational programs, which can be adapted by Islamic schools in various social and cultural contexts.